Navigation efficiency rating of the websites of the Lithuanian Universities - Andziulienė, Beatričė (Lietuvos matematikos rinkinys, 2010)
The paper discusses an effective web site navigation development principles, the effectiveness of navigation, the navigation elements of visual clarity, feedback realization. Outlining the main elements constituting an effective navigation: site orientation, site management, navigational facilities, visual design, navigation efficiency. For the purposes of the checklist approach, carried Lithuanian university Web navigation efficiency analysis.